Social Capital and Crime - Pavićević, Olivera (Zbornik Instituta za kriminološka i sociološka istraživanja, 2026)
The concept of social capital has, in recent decades, been brought into connection with crime research. The relation between these two social phenomena is complex; therefore, we must consider them through their mutual interaction. Some aspects of social capital have shown a significant impact on decreasing the crime rate, taking into account the differences in correlation between various indicators of social capital and specific crime forms. Results of empirical research have confirmed the significance and positive effects of social capital in decreasing criminal choices, but also opportunities to use social capital, in certain circumstances, as a means for promoting and intensifying criminal behaviour.